2000
DOI: 10.1021/ma0008239
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Orientation of p-Methoxyazobenzene Side Chains in Liquid Crystalline Polymer Films by Irradiation with Nonpolarized Light

Abstract: Unambiguous observation of the reorientation of azobenzene chromophores toward the propagation direction of the actinic light has been performed. Prolonged irradiation of a spin-coated film of liquid crystalline poly[6-{4-(4′-methoxyphenyl)azophenyloxy}hexyl methacrylate] (C6MeO) with 436 nm light for n-π* excitation led to a marked decrease of the π-π* absorption band. Spectral analysis in combination with conoscopic observation revealed that the reorientation of the azobenzene chromophores occurs in such a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 36 publications
4
84
0
Order By: Relevance
“…130°C, as previously reported by several groups. [32][33][34] After annealing the sample in the nematic phase and quenching at room temperature, X-ray diffraction studies of the homopolymer P100 film confirmed that the nematic phase was frozen in the glassy state. No diffraction peaks were detected in the angle region in which smectic layer difraction can be expected (Fig.…”
Section: General Properties Of the Azopolymer P100mentioning
confidence: 95%
“…130°C, as previously reported by several groups. [32][33][34] After annealing the sample in the nematic phase and quenching at room temperature, X-ray diffraction studies of the homopolymer P100 film confirmed that the nematic phase was frozen in the glassy state. No diffraction peaks were detected in the angle region in which smectic layer difraction can be expected (Fig.…”
Section: General Properties Of the Azopolymer P100mentioning
confidence: 95%
“…In most cases, these groups are oriented perpendicularly to the polarization plane of the incident light. [5][6][7][8][9][10][11][12][13][14][15][16] The origin of this phenomenon is explained by the process of selective excitation and E-Z-E isomerization cycles of the chromophores oriented predominately along the polarization plane. After many cycles of excitationrelaxation and isomerization accompanied by a rotational diffusion, the assembly of chromophores becomes oriented in the direction perpendicular to the polarization plane.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of publications devoted to the study of photo-orientation phenomena, [5][6][7][8][9][10][11][12][13][14][15][16] the relationship between the molecular structure and photoorientation kinetics, as well as the values of photoinduced dichroism, is still not completely clear. Another important topic for future research in this field is related to the investigation of the effect of the thermal treatment of samples on the kinetics of photo-orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The most common azo polymers are acrylates (Morino et al, 1998), methacrylates (Altomare et al, 2001), and isocyanates (Tsutsumi et al, 1996). Thin films are usually prepared by spincoating (Han and Ichimura, 2001;Blinov et al, 1998;Weh et al, 1998;Ichimura et al, 1996), although there are also many examples of using solvent evaporation, the Langmuir-Blodgett technique (Silva et al, 2002;Razna et al, 1999;Jianhua et al, 1998;Seki et al, 1993), and self-assembled monolayers (Evans et al, 1998). Spin-cast films are typically annealed above the polymer glass transition temperature (T g ) to remove residual solvent and erase any hydrodynamically induced anisotropy.…”
Section: Classes Of Azobenzene Systemsmentioning
confidence: 99%
“…It is unavoidable that chromophores will efficiently build up aligned along the irradiation axis, but this is often ignored in the literature, or characterized as ''photobleaching'' when in fact it is a reversible photoalignment (albeit one that reduces the absorbance as viewed by any photoprobe). Because unpolarized light can photoorient (along the axis of illumination) (Han and Ichimura, 2001), even sunlight is suitable. The motion of the sun through the sky over the course of a day can cause orientation at different tilt angles (Ichimura and Han, 2000).…”
Section: Photoorientationmentioning
confidence: 99%